VALIDITY AND RELIABILITY OF TWO STRAIN GAUGES TO MEASURE UPPER-BODY RELATIVE STRENGTH IN GYMNASTICS STILL RINGSGTH IN GYMNASTICS STILL RINGS - Tom Lecocq; Luis Mochizuki; Arnaud Gouelle; Nicolas Tordi (Science of Gymnastics Journal)
The still rings routine has evolved over the last century, emphasizing increasing strength. What is paramount is not absolute but relative strength, as each gymnast hangs from the still rings and must overcome the effect of gravity on their body using their own upper limb characteristics: strength and dimension. While the vertical force produced by the gymnast is easily measured on a force plate, a specific computation is required when the force is measured in the cable, as the cables are not perfectly vertical. No publication has yet investigated the impact of cable length or the distance between the rings (i.e., the gymnast's arm span) on the tension measured in the cable. The purpose of this study is to validate strain gauges in comparison with a force plate and to provide recommendations for their use in assessing a gymnast's relative strength. To address this, a static loading procedure was performed with weights ranging from 50 to 80 kg, increasing in increments of 10 kg (50, 60, 70, 80 kg). Different distances between the still rings were tested, ranging from 50 cm (vertical cables – 0.0° angle) to 170 cm (31.1° angle), with increments of 20 cm (i.e., 10 cm on each side). Each weight was first placed on a pair of force plates (K-Deltas, Kinvent Biomécanique) before being hung in the middle of the rings with cables equipped with 1-axis strain gauges (K-Pull traction dynamometers, Kinvent Biomécanique). The largest discrepancy between the two methods was 10.31 N, which could be attributed to the sensor as well as the distance between the rings. This article provides a clear answer to the questions regarding the effects of the angle and the length of the cable on tension. Strain gauges are a smaller, lighter, and more affordable alternative to force plates while remaining reliable, valid, and discriminative, provided that the cable angle is known.